2010
DOI: 10.1128/jcm.01720-09
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Melioidosis Cases and Viable Burkholderia pseudomallei in Soil: Evidence for Emerging Melioidosis in Taiwan

Abstract: A survey for the prevalence if Burkholderia pseudomallei in soil in Taiwan found that its incidence is comparable to that in other regions of the world where melioidosis is endemic. The presence of identical genetic patterns among the clinical and environmental isolates evaluated suggested a link between the pathogens present in contaminated soil and the emergence of indigenous melioidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 11 publications
(10 reference statements)
2
39
0
Order By: Relevance
“…Burkholderia pseudomallei vgh19 and B. pseudomallei CD were obtained from melioidosis patients or from soil environments. 19 From information on both strains, refer to the MLST (multilocus sequence typing) database (http://bpseudomallei.mlst.net/). 20 Mouse-derived B. pseudomallei strains NK19_mouse and NKcd_mouse were generated from the parent strains vgh19 and CD, respectively, by repeated intravenous injection into BALB/c mice.…”
Section: Methodsmentioning
confidence: 99%
“…Burkholderia pseudomallei vgh19 and B. pseudomallei CD were obtained from melioidosis patients or from soil environments. 19 From information on both strains, refer to the MLST (multilocus sequence typing) database (http://bpseudomallei.mlst.net/). 20 Mouse-derived B. pseudomallei strains NK19_mouse and NKcd_mouse were generated from the parent strains vgh19 and CD, respectively, by repeated intravenous injection into BALB/c mice.…”
Section: Methodsmentioning
confidence: 99%
“…Melioidosis is an infectious disease caused by Burkholderia pseudomallei, a Gram-negative saprophytic soil bacterium (2,3,4,25,26,30). The majority of patients are reported in southeast Asia and northern Australia (3,4,25,26).…”
mentioning
confidence: 99%
“…Chen et al recommends the fliC method with the possible addition of another PCR method (Dharakul et al, 1999) for detection of B. pseudomallei in soil samples. In fact, two epidemiological studies used Wajanarogana et al's and Dharakul et al's assays and reported that PCR was usually inferior to serology, but superior to culture in detecting B. pseudomallei in soil samples (Su et al, 2007;Chen et al, 2010). Chen et al's epidemiological study revealed 53 soil samples that were confirmed positive by Wajanarogana et al's and Dharakul et al's tests, but were negative by culture, indicating PCR sensitivity beyond culture (Chen et al, 2010 .…”
Section: Pcr Methods To Detect and Differentiate The Burkholderia Psementioning
confidence: 94%
“…In fact, two epidemiological studies used Wajanarogana et al's and Dharakul et al's assays and reported that PCR was usually inferior to serology, but superior to culture in detecting B. pseudomallei in soil samples (Su et al, 2007;Chen et al, 2010). Chen et al's epidemiological study revealed 53 soil samples that were confirmed positive by Wajanarogana et al's and Dharakul et al's tests, but were negative by culture, indicating PCR sensitivity beyond culture (Chen et al, 2010 . Overall, 122018 produced a sensitivity of 100% and a specificity of 98.4%, due to six false positives detected by the B. pseudomallei specific probe.…”
Section: Pcr Methods To Detect and Differentiate The Burkholderia Psementioning
confidence: 94%
See 1 more Smart Citation